Principles of robotics: regulating robots in the real world. Issue 2 (3rd April 2017) - Boden, Margaret; Bryson, Joanna; Caldwell, Darwin; Dautenhahn, Kerstin; Edwards, Lilian; Kember, Sarah; Newman, Paul; Parry, Vivienne; Pegman, Geoff; Rodden, Tom; Sorrell, Tom; Wallis, Mick; et al.
ABSTRACT: This paper proposes a set of five ethical principles, together with seven high-level messages, as a basis for responsible robotics. The Principles of Robotics were drafted in 2010 and published online in 2011. Since then the principles have influenced, and continue to influence, a number of initiatives in robot ethics but have not, to date, been formally published. This paper remedies that omission.